ANTIOXIDANT AND ANTIPROLIFERATIVE ACTIVITIES OF DIFFERENT CULTIVARS OF TOMATOES (LYCOPERSICON ESCULENTUM) ON TUMORAL CELL LINES - Tommonaro, Giuseppina; Piscitelli, Concetta; Lavorgna, Margherita; Isidori, Marina; Russo, Chiara; Prisco, Rocco De; Abbamondi, Gennaro Roberto; Iodice, Carmine (JOURNAL OF ADVANCES IN BIOLOGY, 2017)
To increase the knowledge about the biological properties of tomatoes, the antioxidant and antiproliferative activities of extracts of nine cultivars of Lycopersicon esculentum, as well as their chemical composition, were studied. The highest antioxidant capacity has been revealed in San Marzano Cirio 3 and Pomodoro Giallo cultivars, both in hydrophilic and lipophilic fractions, while San Marzano, Corbarino di Corbara, and Pomodoro Giallo exhibited the best radical scavenger activity in methanolic fraction. As regards the antiproliferative activity, the median inhibition concentrations of the lipophilic extracts ranged from 272.3 (Pomodoro Giallo) to 364.4 (Corbarino di Corbara) mg dried extract L-1 on Hep-G2 and from 324.6 (San Marzano Cirio 3) to 455.4 (Nero di Sicilia) on Caco-2. The methanolic extracts were more active on Caco-2 than Hep-G2, while the hydrophilic extracts were not active. These biological properties could be ascribed to the identified carotenoids and phenolic acids as well as to a pull of minor compounds exerting their synergistic effect.